2000
DOI: 10.1109/38.844372
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive routing for road traffic

Abstract: An integrated system uses road congestion information to guide routing. GPS tracks vehicles, and the GSM short message service maintains communications with a central planning service.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 6 publications
0
36
0
Order By: Relevance
“…Whereas an exhaustive search would find the guaranteed shortest path, the time required to calculate this route would increase dramatically for each increment in the size of the underlying transport data [13]. A secondary benefit of this search algorithm is that the addition of any new modes of transport to the iTransIT framework is not expected to effect the performance, or the computational cost incurred by the STIS platform.…”
Section: Generating Journey Routesmentioning
confidence: 99%
“…Whereas an exhaustive search would find the guaranteed shortest path, the time required to calculate this route would increase dramatically for each increment in the size of the underlying transport data [13]. A secondary benefit of this search algorithm is that the addition of any new modes of transport to the iTransIT framework is not expected to effect the performance, or the computational cost incurred by the STIS platform.…”
Section: Generating Journey Routesmentioning
confidence: 99%
“…In CTP, the goal is to find the minimum expected length path over a finite graph whose edges are marked with their respective probabilities of being traversable and each edge's status can be discovered dynamically when encountered. SOSP and CTP have practical applications in important probabilistic path-planning environments such as robot navigation in stochastic domains (Blei and Kaelbling 1999, Ferguson et al 2004, Likhachev et al 2005, minefield countermeasures (Smith 1995, Witherspoon et al 1995, and adaptive traffic routing (Fawcett andRobinson 2000, Gao andChabini 2006). In fact, both problems as well as closely related ones have gained considerable attention recentlysee, e.g., Nikolova and Karger (2008), Eyerich et al (2009), Likhachev and Stentz (2009), Xu et al (2009), Aksakalli and Ceyhan (2012).…”
Section: Introductionmentioning
confidence: 99%
“…[2]) or the least congested route (e.g. [3]) is chosen, however, some studies (e.g. [4]) showed that the road geometry and the condition of the road infrastructure can significantly affect fuel economy.…”
Section: Introductionmentioning
confidence: 99%